Echocardiography in Type II Diabetes Mellitus- A Prospective Study in Industrial Population - Sarma, Amiejo KR (Nepalese Heart Journal, 2004)
The early detection of the myocardial manifestation in Diabetes Mellitus (DM) is of considerable importance, since the prognosis of patients with DM generally determined by the secondary cardiac complications. The aim of this study was to investigate whether asymptomatic patients with Type Il diabetes Mellitus without apparent clinical heart disease show any detectable abnormality in Echocardiography.